2005
DOI: 10.1038/sj.onc.1208271
|View full text |Cite
|
Sign up to set email alerts
|

Yeast polo-like kinases: functionally conserved multitask mitotic regulators

Abstract: The polo-like kinases (Plks) are a conserved subfamily of Ser/Thr protein kinases that play pivotal roles in regulating various cellular and biochemical events at multiple stages of M phase. Genetic and biochemical data revealed that both the budding yeast and the fission yeast polo kinase homologs (Cdc5 and Plo1, respectively) bear remarkable functional similarities with those in metazoan organisms, suggesting that the role of Plks is largely conserved throughout evolution. Thus, studies on Plks in geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 181 publications
(229 reference statements)
2
61
0
Order By: Relevance
“…Animal PLKs act late in meiosis during spermatogenesis and oocyte maturation, mainly regulating events associated with the two meiotic divisions (Lee and Amon 2003a;Liu et al 2007). Animal PLK is also present earlier, during meiosis I prophase, but little is known about its function at this earlier stage (Matsubara et al 1995;Mirouse et al 2006).Budding yeast PLK, Cdc5, plays essential roles in the exit from mitosis and in cytokinesis (Lee et al 2005). Studies using conditional alleles and alleles that express CDC5 during mitosis but not during meiosis (cdc5-mn, meiotic null) have revealed meiosis I prophase functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Animal PLKs act late in meiosis during spermatogenesis and oocyte maturation, mainly regulating events associated with the two meiotic divisions (Lee and Amon 2003a;Liu et al 2007). Animal PLK is also present earlier, during meiosis I prophase, but little is known about its function at this earlier stage (Matsubara et al 1995;Mirouse et al 2006).Budding yeast PLK, Cdc5, plays essential roles in the exit from mitosis and in cytokinesis (Lee et al 2005). Studies using conditional alleles and alleles that express CDC5 during mitosis but not during meiosis (cdc5-mn, meiotic null) have revealed meiosis I prophase functions.…”
mentioning
confidence: 99%
“…Budding yeast PLK, Cdc5, plays essential roles in the exit from mitosis and in cytokinesis (Lee et al 2005). Studies using conditional alleles and alleles that express CDC5 during mitosis but not during meiosis (cdc5-mn, meiotic null) have revealed meiosis I prophase functions.…”
mentioning
confidence: 99%
“…Cdc5 regulates G2 to M phase transition [7], metaphase to anaphase transition during mitosis [8,9], exit from mitosis and cytokinesis [9]. Cdc5 also plays an important role during meiosis in yeast [10].…”
Section: * Corresponding Author Email: Asourirajan@gmailcom Phone: mentioning
confidence: 99%
“…23 If Clb2-Cdc28 activity is critical for inducing the ultimate action of Cdc5-dependent Swe1 hyperphosphorylation, then how is Clb2-Cdc28 capable of priming Swe1 under the conditions where unphosphorylated, stable, Swe1 potently inhibits Clb2-Cdc28 itself? One possibility is that a low level of Clb2-Cdc28 activity may be sufficient to initiate the priming modification, which will then be reinforced as the level of Clb2 rises at the late stage of the cell cycle.…”
Section: Concerted Action Of Clb2-cdc28 and Cdc5 In Swe1 Regulationmentioning
confidence: 99%
“…21 Cla4 associates tightly with septins 22 early in the cell cycle and promotes septin filament assembly at the bud neck, whereas Cdc5 localizes to the bud-neck late in the cell cycle after first appearing at the spindle pole bodies (SPBs). 23 As with the timing of their localization to the bud-neck, acute inhibition of Cla4 activity diminished early phosphorylation of Swe1, whereas depletion of Cdc5 activity prevented hyperphosphorylation of Swe1 species that are already moderately phosphorylated. 21 Consistently, close examination of a viable cdc5-3 CDC14 TAB6-1 mutant (CDC14 TAB6-1 bypasses the mitotic exit defect, but not the G 2 /M defect, of the cdc5-3 allele 24 ) revealed that this mutant proceeds through the cell cycle but with a significant delay in Swe1 degradation at elevated temperatures (Fig.…”
Section: Cla4 and Cdc5 Phosphorylates Swe1 At Two Distinct Stages Of mentioning
confidence: 99%